Problematic Difficulties in Reading Arabic Texts for Students tt MTs DDI Salumbia - Amanda; Harun, Ubay; Sitti Hasnah (Albariq: Jurnal Pendidikan Bahasa Arab, 2025)
Many students at the junior secondary level, especially in grade VIII at MTs DDI Salumbia, experience difficulties in reading Arabic texts. These difficulties affect the effectiveness of learning and students' understanding of Arabic language materials. This study aims to describe the problems related to difficulties in reading Arabic texts, analyze the causal factors, and identify the most effective solutions to address these problems. This research employed a descriptive qualitative approach involving Arabic language teachers and grade VIII students of MTs DDI Salumbia. Data were collected through observation, interviews, and documentation. The findings revealed that students’ reading difficulties stemmed from internal factors, such as limited ability to read the Qur'an and lack of recognition of Hijaiyah letters, as well as external factors, including the shortage of qualified Arabic teachers and an unsupportive learning environment. Proposed solutions include school collaboration with universities or Islamic boarding schools to recruit Arabic language teachers, creating a school environment that supports Arabic language habituation, and strengthening students’ foundational skills through tahsin training, iqra learning, and small group guidance.